Rebranding and Product Mix Effects on The Listeners Satisfaction on KIS FM Radio Jakarta - Oktara, Bayu; Kurniawati; Putri, Kinkin Yuliaty S (CV ODIS, 2021)
In 2016, Nielsen released a report that Radio Still Has a Place in the Hearts of Its Listeners. However, data from the company of Radio Kis 95.1 FM shows a decline in the number of listeners. This decline rate reflects satisfaction level of radio listeners. In 2017, PT Mahaka Radio Integra acquired the shares of PT Radio Kirana Insan Utama (KIS FM) from the Ramako Group, to strengthen the listener base, provide a variety of integrated advertising services and form a solid foundation for market change. The company carried out a rebranding strategy with new targets, segmentation, and positioning. The rebranding includes the colors, logos designs, terms, and product mixes. The various product mixes are reflected in programs, music formats and broadcasters. This strategy is intended to increase listener satisfaction. This research to prove how rebranding and product mix can affect listener satisfaction uses descriptive quantitative research method with a causal relationship approach. Problem formulation and formulation of hypotheses using rebranding variables, product mix and listener satisfaction of Kis-FM Jakarta radio. The data was obtained through a field survey using a questionnaire, then analyzed and described the research problems through data analysis, statistical calculations, and data interpretation. The results showed that rebranding, mediated by product mix, had a significant effect on listener satisfaction of Kis 95.1 FM Jakarta. So, the products that offered to the customers are broadcasting programs which involving the listeners, songs according to segmentation targets, broadcasters who are active on social media, content on other platforms such as Instagram, Twitter, Facebook, YouTube, Podcasts and the use of internet technology for live streaming either through websites or digital applications. This is done with considering radio statios as media has to adapt with internet-based innovation or digital information technology to meet the needs and increase listener satisfaction.